The Use of Grammarly to Increase Students Writing Skills in Writing Descriptive Text - Wulandari, Kristina Fitri; Yuliana, Yohanes Gatot Sutapa; Surmiyati, Surmiyati (Universitas Cokroaminoto Palopo, 2025)
Writing skills are one of the skills students learn at the senior high school level. This research aims to discover how Grammarly can increase students' writing skills in writing descriptive text for the tenth-grade students of SMAN 01 Sekadau Hilir. This research was done using a pre-experimental design that used one group of pretest and post-test types. The research findings showed that the t-test result with the degree of freedom (df) = 35 and significant level (α = 0.05) was 15.07, and the t-table was 1.690. It shows that the t-test was higher than the t-table (15.07 > 1.690). It can be inferred that the use of Grammarly to increase students' writing skills in writing descriptive text is effective. It can be concluded that the alternative hypothesis (Ha) is accepted while the null hypothesis (Ho) is rejected. Furthermore, the result of the effect size was 2.51, which is categorized as a strong effect. Therefore, the use of Grammarly to increase students' writing skills in writing descriptive text was effective with a significant effect.